Deciphering the Role of CBF/DREB Transcription Factors and Dehydrins in Maintaining the Quality of Table Grapes cv. Autumn Royal Treated with High CO2 Levels and Stored at 0°C - Vazquez-Hernandez, Maria; Romero, Irene; Escribano, M. I.; Merodio, Carmen; Sanchez-Ballesta, M. T. (Frontiers in Plant Science, 2017)
C-repeat/dehydration-responsive element binding factors (CBF/DREB) are transcription factors which play a role in improving plant cold stress resistance and recognize the DRE/CRT element in the promoter of a set of cold regulated genes. Dehydrins (DHNs) are proteins that accumulate in plants in response to cold stress, which present, in some cases, CBF/DREB recognition sequences in their promoters and are activated by members of this transcription factor family. The application of a 3-day gaseous treatment with 20 kPa CO2 at 0°C to table grapes cv. Autumn Royal maintained the quality of the bunches during postharvest storage at 0°C, reducing weight loss and rachis browning. In order to determine the role of CBF/DREB genes in the beneficial effect of the gaseous treatment by regulating DHNs, we have analyzed the gene expression pattern of three VviDREBA1s (VviDREBA1-1, VviDREBA1-6, and VviDREBA1-7) as well as three VviDHNs (VviDHN1a, VviDHN2, and VviDHN4), in both alternative splicing forms. Results showed that the differences in VviDREBA1s expression were tissue and atmosphere composition dependent, although the application of high levels of CO2 caused a greater increase of VviDREBA1-1 in the skin, VviDREBA1-6 in the pulp and VviDREBA1-7 in the skin and pulp. Likewise, the application of high levels of CO2 regulated the retention of introns in the transcripts of the dehydrins studied in the different tissues analyzed. The DHNs promoter analysis showed that VviDHN2 presented the cis-acting DRE and CRT elements, whereas VviDHN1a presented only the DRE motif. Our electrophoretic mobility shift assays (EMSA) showed that VviDREBA1-1 was the only transcription factor that had in vitro binding capacity to the CRT element of the VviDHN2 promoter region, indicating that the transcriptional regulation of VviDHN1a and VviDHN4 would be carried out by activating other independent routes of these transcription factors. Our results suggest that the application of high CO2 levels to maintain table grape quality during storage at 0°C, leads to an activation of CBF/DREBs transcription factors. Among these factors, VviDREBA1-1 seems to participate in the transcriptional activation of VviDHN2 via CRT binding, with the unspliced form of this DHN being activated by high CO2 levels in all the tissues analyzed.